THE EFFECTS OF PRACTICAL TEACHING ON STUDENTS’ MORPHOLOGICAL DIMENSIONS - Ratko Pavlović (Sport Mont, 2010)
The anthropological space of a human being is multidimensional and as such susceptible to certain transformational processes, especially if these processes serve to accomplish a clearly defined goal. One of the features of anthropological space, rather susceptible to changes, is a morphological space and, in particular, some segments of it. The research is carried out on the sample of ninety freshmen. The effects of practical teaching on students’ morphological dimensions were studied during one semester. It was necessary to use ten different variables for this research, out of which six variables were used to define voluminousness and body mass, and five variables for defining subcutaneous fat tissue. In order to obtain relevant information we applied univariant and multivariante analysis of the variance (ANOVA/MANOVA), which confirmed positive effects of the teaching and statistically relevant transformation of a change in relation to the initial condition of a respondent.